Grounded by MCO, UMP student finally return home - UMP, PNC (2020)
The first batch of 1,154 students from Universiti Malaysia Pahang (UMP), public and private universities, polytechnic and community college has started their journey back to hometowns in east coast region on 30 April 2020.